Thompson & Thompson genetics in medicine : Robert L. Nussbaum, Roderick R. McInnes, Huntington F. Willard ; with clinical case studies updated and new cases prepared by Ada Hamosh - Nussbaum, Robert L. , 1950-; McInnes, Roderick R.; Willard, Huntington F. (Saunders, Elsevier, 2007)
Clearly written and illustrated throughout, the seventh edition retains all of the features that have made its predecessors so popular while also detailing all of the new developments and advances in the field. Readers can also access the complete contents and more online at www.studentconsult.com